Both subthalamic and pallidal deep brain stimulation are effective for GNAO1-associated dystonia: three case reports and a literature review. (April 2022) - Liu, Ye; Zhang, Qingping; Wang, Jun; Liu, Jiyuan; Yang, Wuyang; Yan, Xuejing; Ouyang, Yi; Yang, Haibo
Background: Mutations in the G-protein subunit alpha o1 ( GNAO1 ) gene have recently been shown to be involved in the pathogenesis of early infantile epileptic encephalopathy and movement disorders. The clinical manifestations of GNAO1 -associated movement disorders are highly heterogeneous. However, the genotype–phenotype correlations in this disease remain unclear, and the treatments for GNAO1 -associated movement disorders are still limited. Objective: The objective of this study was to explore diagnostic and therapeutic strategies for GNAO1 -associated movement disorders. Methods: This study describes the cases of three Chinese patients who had shown severe and progressive dystonia in the absence of epilepsy since early childhood. We performed genetic analyses in these patients. Patients 1 and 2 underwent globus pallidus internus (GPi) deep brain stimulation (DBS) implantation, and Patient 3 underwent subthalamic nucleus (STN) DBS implantation. In addition, on the basis of a literature review, we summarized and discussed the clinical characteristics and outcomes after DBS surgery for all reported patients with GNAO1 -associated movement disorders. Results: Whole-exome sequencing (WES) analysis revealed de novo variants in the GNAO1 gene for all three patients, including a splice-site variant (c.724–8G > A) in Patients 1 and 3 and a novel heterozygous missense variant (c.124G > A; p. Gly42Arg) in Patient 2. Both GPi and STN DBS were effective in improving the dystonia symptoms of all three patients. Conclusion: DBS is effective in ameliorating motor symptoms in patients with GNAO1 -associated movement disorders, and both STN DBS and GPi DBS should be considered promptly for patients with sustained refractory GNAO1 -associated dystonia.